Influence of Propofol on Hemodynamics During Cesarean Section (Texas Journal of Multidisciplinary Studies, 2023)
The article presents the results of assessing the degree of influence of propofol anesthesia on the cardiovascular system of parturient women during surgical delivery in 98 pregnant women. The CH of parturient women undergoes significant changes at various stages of anesthesia. During induction of anesthesia, there is a tendency towards a decrease in cardiac output and minute performance, a decrease in systemic arterial tone, which was accompanied by a tendency to arterial hypotension and compensatory tachycardia. These changes were transient in nature and did not lead to gross hemodynamic changes, by the time the surgical intervention is completed, all the main CH indicators return to their original values.